2016
DOI: 10.1016/j.bbamem.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic acid reduces membrane fluidity, inhibits cholesterol domain formation, and normalizes bilayer width in atherosclerotic-like model membranes

Abstract: Cholesterol crystalline domains characterize atherosclerotic membranes, altering vascular signaling and function. Omega-3 fatty acids reduce membrane lipid peroxidation and subsequent cholesterol domain formation. We evaluated non-peroxidation-mediated effects of eicosapentaenoic acid (EPA), other TG-lowering agents, docosahexaenoic acid (DHA), and other long-chain fatty acids on membrane fluidity, bilayer width, and cholesterol domain formation in model membranes. In membranes prepared at 1.5:1 cholesterol-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(128 citation statements)
references
References 67 publications
5
122
0
1
Order By: Relevance
“…Membrane models have suggested that EPA and DHA have different molecular locations and orientations resulting in distinct membrane structures which may confer different biological activities [70]. Differences in membrane interactions between EPA and DHA may result in the inhibition of cholesterol crystalline domains by EPA but not DHA, which may impact endothelial function [71]. Furthermore, EPA is more efficiently incorporated into HDL particles than DHA which prolongs and increases EPA's ability to inhibit HDL oxidation compared with DHA [72].…”
Section: Clinical Utility Of the Epa:aa Ratiomentioning
confidence: 99%
“…Membrane models have suggested that EPA and DHA have different molecular locations and orientations resulting in distinct membrane structures which may confer different biological activities [70]. Differences in membrane interactions between EPA and DHA may result in the inhibition of cholesterol crystalline domains by EPA but not DHA, which may impact endothelial function [71]. Furthermore, EPA is more efficiently incorporated into HDL particles than DHA which prolongs and increases EPA's ability to inhibit HDL oxidation compared with DHA [72].…”
Section: Clinical Utility Of the Epa:aa Ratiomentioning
confidence: 99%
“…29,30 When incorporated into cell membranes, EPA confers membrane stability even in the setting of increased cholesterol load, which in turn imparts a protective effect against endothelial dysfunction. 31 Moreover, higher concentration of EPA found in atherosclerotic plaques has been shown to be associated with less foam cells and a decrease in the expression of matrix metalloproteinases, which are thought to increase plaque stability. 32 EPA Effects on Cardiovascular Outcomes (Table 2) The first cardiovascular outcomes trial on EPA was the Japan EPA Lipid Intervention Study (JELIS) study published in 2007.…”
Section: From Fish-to-fish Oil: a Historical Contextmentioning
confidence: 99%
“…Additionally, recent mechanistic studies have shown that minor changes in the EPA content of endothelial membranes may markedly alter the biophysical properties of the membrane [28]. Furthermore, changes in membrane fluidity, thickness, and deformability induced by modifications to lipid dynamics and/or structural organization can profoundly impact endothelial function [29].…”
Section: Role Of Epa In Microvascular Thromboinflammationmentioning
confidence: 99%
“…Although the role of DHA neurolipidomics in neurovascular coupling appears to be underestimated, substantial experimental evidence suggests that the morphologic and functional integrity of the neurovascular unit largely depends on high DHA enrichment [37,40,43]. Moreover, the potential role of EPA in microvascular function further supports the evolutionary importance of these essential nutrients to maintain efficient functional couplings between neural and vascular networks [28,29]. A functional neurovascular unit may be crucial not only for neurovascular coupling but also for BBB integrity and neurogenesis.…”
Section: Dha and Neurovascular Unitmentioning
confidence: 99%